Makiusap sa Diyos - Brocka, Lino. (Quezon City Regal Films)
Dolores, a kindhearted novitiate devoted to her faith, sees her life take a turn for the worse after becoming the victim of rape. And instead of gaining sympathy, she punished by her superiors to something she did not will, prompting her to flee the nunnery.
VCD
Christopher De Leon, Gabby Concepcion, Ruffa Gutierrez.
Keywords: Feature films; Drama